KORELASI INDEKS MASA TUBUH DENGAN SIKLUS MENSTRUASI PADA MAHASISWA AKADEMI KEBIDANAN YLPP PURWOKERTO - Trisnawati, Yuli; Anasari, Tri (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2018)
Menstruation is the primary sexual sign that marks the period of puberty for a woman. Menstrual cycle disorders often occur in adolescents and are caused by several factors including psychological, hormonal, genetic disorders, organic abnormalities and nutritional status. High or low body mass index can cause menstrual disorders including absence of menstruation or amenorrhea, irregular periods and pain during menstruation. The purpose of this study was to find out the distribution of body mass index in respondents, to know the distribution of cycles of menstruation of respondents, and to know the relation of body mass index (IMT) with the regularity of menstrual cycle. Type of research: research used is descriptive research type with cross sectional approach method. The total population is 82 students, then the sampling is done by accidental sample sampling technique to 41 respondents. Instruments in this study using questionnaires and data analysis using chi square analysis. Results: Most of the body mass index (BMI) of respondents was normal (73%), most (60%) had regular menstrual cycles, and there was a relationship between body mass index and regular menstrual cycle with nilap p = 0,000. Keywords: body mass index, cycle of menstruation